TAFSIR LUGHAWI - Syafrijal, Syafrijal (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
Lughawi Tafsir (Quranic Interpretation) explains the Holy Qurâan through semiotic and semantic including language, morphology, lexical, grammatical, and rhetoric.Â This kind of interpretation has been used by Mufassir (experts in Quranic Interpretastion) to explain the verses of the Quran.Â Since the Quran was written in a very high style of language, the mufassirs who applied this method should have capability with certain criteria.The Lughawi Tafsir appeared in 2nd and 3rd H, along with the integration of the Arabs and non-Arabians.Â The fact that Arabic was no longer superior language of that time and the decrease of zaug âarabi (sense of Arabic), necessitated the Mufassirs to strengthen the language so that they could figure out the meanings of the Qurâan. The operational concept in explaining Lughawi Tafsir is done by presenting topics in the fields of nahu, sharaf, and balaghah together with their types and branches.CopyrightÂ Â©Â 2013 by Al-TalimÂ AllÂ rightÂ reservedDOI:Â 10.15548/jt.v20i2.39